Influence of female age of Trichogramma cacoeciae and host eggs age on its parasitic effectiveness - Vourlioti, F.; Milonas, P. G. (ENTOMOLOGIA HELLENICA, 2006)
Laboratory experiments were conducted to investigate the influence of female age of Trichogramma cacoeciae (Marchai) (Hymenoptera: Trichogrammatidae) and egg age of Lobesia bot rana (Denis & Schiffermueller) (Lepidoptera: Tortricidae) on parasitoid effectiveness. It was found that T. cacoecciae females parasitize more frequently 4 days old L. boi rana eggs than younger ones. Furthermore, developmental time of their offspring retarded and percentage of viable eggs decreased when parasitoid larvae fed with older eggs. 7*. cacoecciae females that were 4 days old were more effective in parasitising L. botrana eggs. Rearing the paras ito ids on Sitôt roga ce rea lei la eggs for one generation resulted in a decreased number of parasitised eggs of L boi rana than when reared on Ephestia kit eh niella eggs. The implications of these results in selecting a candidate species for biological control are discussed.